Solve for x: 5^(3x + 24) = 1

Luz Stokes 2022-07-27 Answered
Solve for x:
5 3 x + 24 = 1
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Bradley Sherman
Answered 2022-07-28 Author has 17 answers
Consider the equation 5 3 x + 24 = 1
Taking natural logarithms bot sides:
ln 5 3 x + 24 = ln 1 ln 5 3 x + 24 = 0 ( 3 x + 24 ) ln 5 = 0 3 x + 24 = 0 3 x = 24 x = 24 3 x = 8
Therefore, the solution is x=-8
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2022-08-02
If log sub(a)10 = 0.250, then log sub(10)a equals ?
Breakdown:
log sub(a)10 = 0.250
The solution requires me to the take the base(a) antilogarithmof both sides. That would be
10 = a 0.250 .
asked 2022-09-04
Rewrite as a single log with a coefficient of one.
( 4 ln ( x ) ) ( 3 ln ( x ) ) + ( 1 / 4 ln ( x ) )
asked 2021-10-18
Use The Properties Of Logarithms To Simplify
log23.2log20.025
asked 2022-05-21
Simplifying an expression using a logarithm
I have the following expression
1 1 + ρ ( 1 + n ) ( 1 σ ) ( 1 + γ A ) 1 σ < 1
and have to use logarithms to get the following
( 1 σ ) ( n + γ A ) < ρ
Could someone please offer me some help on how to do it? That's a homework question in Macroeconomics - we got the solutions and were told to use the logarithms to get them. However, I'm struggling with the complete procedure, so any help is more than welcome.
Thanks!
asked 2022-03-12
What is the simple way to show that
Nlog{N}klog{k}logk!{N!}
I tried to use the factorial and the log rules but..
Thanks.
asked 2022-05-14
Asymptotics of logarithms of functions
If I know that lim x f ( x ) g ( x ) = 1, does it follow that lim x log f ( x ) log g ( x ) = 1 as well? I see that this definitely doesn't hold for e f ( x ) e g ( x ) (take f ( x ) = x + 1 and g ( x ) = x), but I'm not sure how to handle the other direction.
asked 2022-05-19
simplify the following logarithm and roots expression
please , I need help to solve this problem Can anyone solve it simplify the following
log 729 1 39 ( 1 27 ) 4 3 4
thank in advance to all